Dengue fever [ episode 5 - Foley, Liz; Smith, Jaso; Wilson, Richard; Wood, Laurence; BBC Worldwide (London : BBC Worldwide, 2005)
Dengue fever is a mosquito-borne infection, which affects some 50 million people annually. It is now endemic in more than 100 countries in Africa, South America, the Eastern Mediterranean, Southeast Asia, and the Western Pacific. This program journeys to Thailand to join scientists at the forefront of the fight to contain and eliminate Dengue. Viewers learn about one of the principal challenges involved: the Dengue virus is made up of four different serotypes, and any vaccine must address all four to be effective. Since this has been a steep roadblock, some researchers are trying another approach: fighting the mosquito carriers directly with a naturally occurring bacteria that may lower infection rates
Directed & producer by Jaso Smith; executive producer, Richard Wilson; productrion co-ordinator, Liz Foley
Narrator, Richard Wilson
Keywords: Dengue; Dengue viruses